Небеса обетованные: [Художеств. фильм] / Режиссер-постановщик Э. Рязанов, Гл. оператор Л. Калашников, Худож.-постановщики А. Борисов, С. Иванов - Альтман Г. (Фильмы Эльдара Рязанова, 1999)
Экземпляры: ИСК (20020927) / Инвентарный номер: вкас316 / Цена: 108.60 / Сис.шифр: 85.374.9 / Авт.знак: Н 39 / ГРНТИ: 18 / ББК: 85.374.9(2)